Book Reviews: Z. Piątek, Ekofilozofia, Kraków 2008 - Fiut, Ignacy S. (Problemy Ekorozwoju, 2009)
The advantage of the work is undoubtedly the discourse of arguments, the precise language of the author, but above all, the knowledge of problems from both a philosophical, biological and ecological point of view, which take the form of reliable argumentation on of the theses being proclaimed. It is therefore worth inviting thinkers and researchers to further discuss this inspiring, but also intriguing philosophical proposal introducing eco-philosophical thinking into the 21st century.